Government size and risk premium - Abhishek Kumar; Sushanta Kumar Mallick (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Given the rise in the government debt level in recent times, this paper aims to examine the effect of an increase in government size on risk premium and its transmission in the economy. We jointly identify the term spread shock (originating at the short end and the long end) and the government size shock, using max share identification. Term spread shock originating at the long end is driven by higher risk premium, unlike the shock originating at the short end, and increases inflation and reduces growth. The results suggest that the increase in the share of government expenditure in GDP (size) increases long-term rates by increasing the risk (term premium) and hence obstructs the transmission of monetary policy. As expected, the effect of government size on risk premium is more pronounced during recessions compared to expansions. By including a news shock about future economic activity, we rule out that the effect of government size shock on term premium is not driven by a news shock. We estimate the parameters of a New Keynesian model with term premium by matching the responses in data with responses from the model. The model can generate a similar rise in risk premium due to the increase in government size, and the estimated parameters suggest that the coefficient of risk aversion during recession is more than twice that of during expansions.
Keywords: E43; H11; H12; 330; government debt; interaction between fiscal and monetary policy; fiscal consolidation